Y.Y. Kuch. Economic Planning and Local Mobilization in Post-Mao China, Londres, Contemporary China Institute, School of Oriental and African Studies, University of London, 1985, xii + 57 pp. (Research Notes and Studies num. 7) - Cornejo Bustamante, Romer (El Colegio de México, 1985)
-